Academic language mastery : conversational discourse in context - Zwiers, Jeff; Soto, Ivannia (Thousand Oaks : Corwin, 2017)
By now it's a given: if we're to help our ELLs and SELs access the rigorous demands of today's content standards, we must cultivate the'code' that drives school success: academic language. Look no further for assistance than this much-anticipated series from Ivannia Soto, in which she invites field authorities Jeff Zwiers, David and Yvonne Freeman, Margarita Calderon, and Noma LeMoine to share every teacher's need-to-know strategies on the four essential components of academic language. The subject of this volume is conversational discourse. Here, Jeff Zwiers reveals the power of academic conversation in helping students develop language, clarify concepts, comprehend complex texts, and fortify thinking and relational skills. With this book as your roadmap, you'll learn how to: Foster the skills and language students must develop for productive interactions Implement strategies for scaffolding paired conversations Assess student's oral language development as you go It's imperative that our ELLs and SELs practice academic language in rich conversations with others in school, especially when our classrooms may be their only opportunities to receive modeling, scaffolding, and feedback focused on effective discourse. This book, in concert with the other three volumes in the series, can provide both a foundation and a framework for accelerating the learning of diverse students across grade levels and disciplines.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Academic language -- Study and teaching -- United States; English language -- Study and teaching -- Foreign speakers; People with social disabilities -- Education -- United States; Linguistic minorities -- Education -- United States; English teachers -- Training of -- United States